2012
DOI: 10.19030/jabr.v28i6.7354
|View full text |Cite
|
Sign up to set email alerts
|

The Use Of Capital Budgeting And Cost Of Capital Estimation Methods In Swedish-Listed Companies

Abstract: In this paper Swedish listed companies' use of capital budgeting and cost of capital estimation methods in 2005 and 2008 are examined. The relation between company characteristics and choice of methods is investigated and both within-country longitudinal and cross-country comparisons are made. Larger companies seem to have used capital budgeting methods more frequently than smaller companies. When compared to U.S. and continental European companies, Swedish listed companies employed capital budgeting methods l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 44 publications
(83 reference statements)
3
14
0
Order By: Relevance
“…The use of capital budgeting methods by U.S. and European listed companies has been studied extensively (e.g., besides those already mentioned, Pike, 1988Pike, , 1989Pike, , 1996Pike and Sharp, 1989;Sangster, 1993;Block, 2007;Hermes et al, 2007). [1] There have also been some earlier studies of Sweden (Renck, 1966;Tell, 1978;Yard, 1987;Andersson, 1994;Segelod, 1995;Sandahl and Sjögren, 2003;Holmén and Pramborg, 2009;Hartwig, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of capital budgeting methods by U.S. and European listed companies has been studied extensively (e.g., besides those already mentioned, Pike, 1988Pike, , 1989Pike, , 1996Pike and Sharp, 1989;Sangster, 1993;Block, 2007;Hermes et al, 2007). [1] There have also been some earlier studies of Sweden (Renck, 1966;Tell, 1978;Yard, 1987;Andersson, 1994;Segelod, 1995;Sandahl and Sjögren, 2003;Holmén and Pramborg, 2009;Hartwig, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…[2] Most studies thus explore only use or non-use, or the frequency of use, of capital budgeting methods, and not the association between use and independent variables. When relationships between use and independent variables have been studied (e.g., Hartwig, 2012), only descriptive statistical methods such as correlation analysis and independent-samples t-tests are utilised, so the results cannot be interpreted causally [3].…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have highlighted different business characteristics and their influence on investment decisions practices for large as well as small businesses (Graham & Harvey, 2001;Anand (2002); Brounen et al,2004;Fernando, 2005;Danielson & Scott, 2006;Leon et al,2008;Truong et al, 2008;Brijlal & Quesada, 2009;Pal & Verma, 2011;Daunfeldt & Hartwig, 2012;Hartwig, 2012;Pratheepkanth et al,2013;Ahmed, 2013;Yasmin, 2015;Swarnapali, 2015).…”
Section: Characteristics Of the Businessmentioning
confidence: 99%
“…The size of the business in different studies has been expressed in terms of the number of employees, sales revenue, value of assets, and turnover of the business. Studies conducted by Graham and Harvey (2001), Anand (2002), Brounen et al (2004), Danielson & Scott (2006), Brijlal and Quesada (2009), Daunfeldt and Hartwig (2012), Hartwig (2012), Pratheepkanth et al (2013), and Ahmed (2013) observed that the size of the business influence the choice of investment evaluation techniques. However, there are few studies which contrary to the observation of the above studies observed that size does not affect the choice of investment evaluation techniques (Fernando, 2005;Truong et al, 2008;Leon et al, 2008;Swarnapali, 2015, andYasmin, 2015).…”
Section: Characteristics Of the Businessmentioning
confidence: 99%
See 1 more Smart Citation